Development of Instant Beverage from Predigested Broken Jasmine Brown Rice and Job’s Tears for Diabetic Patients - Yuthavisuthi, Panutporn; Chompreeda, Penkwan; Pirak, Tantawan (Agriculture and Natural Resources, 2012)
At present, there are more than 200 million diabetic patients all over the world who need to have strict dietary control. Therefore, the present research aimed at developing an instant beverage for diabetic patients that provides energy and nutrients appropriate for their needs. A survey of patient’s need for healthy instant beverages revealed that they preferred products that had a natural color and ﬂ avor and a sweet taste, were packed in an aluminum foil sachet and were priced at 7 to 10 baht (USD 1 ≈ 32 baht). Linear programming was employed to formulate the product to obtain the optimum nutrient content and minimize the cost. The optimum formulation of instant beverage for diabetic patients consisted of 35% predigested jasmine brown rice powder, 16% Job’s tears powder, 29.55% full fat milk powder, 13.10% nondairy creamer, 1.3% cocoa powder, 0.05% sucralose, 3.50% erythritol and 1.55% premixed vitamins. A serving of beverage was prepared by mixing powder (35 g) with hot water (140 mL), which yielded protein (5 g), fat (4 g), carbohydrate (22 g) and energy (150 kcal). The cost of a serving of 35 g was 11 baht. The acceptability test showed that almost all of the diabetic patients (99%) accepted the product and 93% of them intended to purchase this product.